PSYCHOLINGUISTIC FACTORS OF SPEECH ACTIVITY OF CHILDREN - Alpanova Shirin (Galaxy International Interdisciplinary Research Journal, 2022)
The article describes the psycholinguistic aspects of children’s speech activity. Aspects of communicative behavior related to the national character, as well as views on its connection with human psychology and physiology, were assessed as an anthropocentric approach to the language system.